A Spirituality of Teacher and Dedication for Disadvantaged Children of Chaowalit Satsamai (Teacher Chaow) - Kaewpluk, Manassawee; Sroysangwan, Watthana; Suwanrawee, Wasinee (Suan Dusit Graduate School Academic Journal, 2022)
The purposes of this research were to study the biography of three life stages, spirituality of teachers. and the practice of dedication to educationally disadvantaged children of Teacher Chaowalit Sadsamai (Kru Chao) by using a qualitative research method. The key informants consisted of 2 parents and 2 youths recruited by purposive selection. The interview and data recording were conducted and the content validity of the interview form was examined by using IOC which had a consistency index between 0.67-1.00. The data were analyzed by descriptive method. The research findings revealed that: 1) The biography and working of Chaowalit Satsamai could be divided into three life stages; Children, he was born with a physical and intellectual disability. Adolescence, he left Rachawadee Home for Persons with Disabilities Protection and Development and he studied at Cholpratansongkroh School, then he graduated with a Bachelor's degree at Kasetsart University. Adult, he found new experiences from newspaper and became a volunteer teacher 2) Teacher spirituality, Chaowalit was regarded as a person with good heart and appreciation for teacher profession, giving love and compassion, taking care of children equally, supporting children according to their potential, listening to reasons, encouraging students to get a higher level of education and being a good role model for society. 3) Regarding the dedication for educationally disadvantaged children, he created partners network with children and parents. Then, he collaborated with other organizations to do activities and grant scholarships which helped raise the quality of children and people’ life in society for the better.